Development of natural fibre for environmental and sustainable advancement. (27th January 2020) - Atiqah, A.; Ansari, M.N.M.; Zahidi, M.M.M.; Begum, S.; Yahya, Zainudin; Alkhadher, Sadeq Abdullah Abdo
The increasing attention on renewable resources for a sustainable environment has led to the expansion in the development of high-performance products made from natural resources. Natural fibres that are diffused in the environment in abundance are economical, making this characteristic a value-added engineering, as they exhibit lower cost and can produce lighter composites, as compared to the existing fibreglass reinforced polymer composites. In this study, the involvement of kenaf fibre in chemical treatment on morphological and mechanical properties of the thermoset polyurethane (PU)-(PUKf) composites was firstly proposed and trialled. The results of chemical treatment on kenaf fibre highlight the improvement on the impact strength although the hardness of kenaf composites is reduced. This is compared with different samples, which are pure thermoset PU and kenaf fibre without chemical treatment. Overall, the developments of natural fibre in engineering and energy sectors could significantly enhance the reduction of solid waste and environmental pollution.